Elements for an agenda of the South : report (South Centre GenevaCH, 1999)
Seeks to highlight key elements in the evolving external environment for development and outlines in broad terms the responses called for from the countries of the South.
Presented to the Twelfth NAM Summit, Durban, South Africa, 1998